Anticancer Effects of Melissa officinalis: A Traditional Medicine - Parviz Faraji; Mostafa Araj-Khodaei; Maryam Ghaffari; Jafar Ezzati Nazhad Dolatabadi (Tabriz University of Medical Sciences, 2022)
Melissa officinalis (M. officinalis) is an herbal-based plant from the family of Lamiaceae and native to Europe and the Mediterranean region, widely used to cure various cancers. Phytochemical investigations proved different compounds such as polyphenolic compounds, flavonoids, and essential oil in the stem and leaves of M. officinalis as main ingredients contributing to different antitumor activity, including antiproliferation and antioxidant antiangiogenetic, antimigratory, antiapoptotic, and change in cell cycle profile of cancer cells. Herbal formulations with colorful ingredients use several types of these mentioned biological processes to display synergistic cancer treatment activities. M. officinalis extracts a wide range from water to ethanol using varied mechanisms to reduce the viability of cancer cells. Hence, scientists are currently interested in evaluating these extracts based on the medical plant to minimize the adverse effects of conventional anti-cancer drugs and discover these mechanisms to pave the way for future studies. This review aimed to discuss the recent studies that M. officinalis have used as an anti-cancer agent to investigate its potential effect on several types of cancer. Therefore, after a short introduction of M. officinalis, we will explain the several biological processes by which M. officinalis exert an anti-cancer effect.